2019
DOI: 10.1177/0033294118825100
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Mother Education Program for the Prevention of Child Neglect

Abstract: In the present research, the aim was to develop, implement, and examine the effectiveness of an education program for mothers for the prevention of child neglect. In the study, the “Mother Education Program to Prevent Child Neglect” was initially designed for implementation and a quasi-experimental design involving pretest/posttest, and one-month follow-up test was implemented to examine the effectiveness of the trial procedure. The study group of the research consisted of 24 mothers (12 mothers in the interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Parents were unaware that they may be neglecting their children, not to mention the negative consequences (Anderst & Dowd, 2010). Previous studies have shown that improving parents' awareness and knowledge of child neglect can effectively protect their children from neglect (Beyazit & Bütün Ayhan, 2019); therefore, future research and parenting intervention programs can educate parents on the definition, types, consequences, and prevention of child neglect in LMICs.…”
Section: Discussionmentioning
confidence: 99%
“…Parents were unaware that they may be neglecting their children, not to mention the negative consequences (Anderst & Dowd, 2010). Previous studies have shown that improving parents' awareness and knowledge of child neglect can effectively protect their children from neglect (Beyazit & Bütün Ayhan, 2019); therefore, future research and parenting intervention programs can educate parents on the definition, types, consequences, and prevention of child neglect in LMICs.…”
Section: Discussionmentioning
confidence: 99%
“…In a study that evaluated whether the training offered to parents about child neglect and abuse was effective, it was put forward that parents' levels of awareness and understanding increased, and this was a permanent increase (Sahillioglu & Akman, 2021). In another study evaluating the effect of a training program offered to mothers, it was found that the training program was effective and had a lasting impact (Bütün Ayhan & Beyazit, 2019). Also, in a meta‐analysis, 23 training programs designed to prevent child neglect and abuse were analysed, and it was discerned that 90 per cent of these training programs were effective in preventing child neglect and abuse (Altafim & Linhares, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…To whom correspondence should be addressed. Manuscript received: 2021-03-01; revised: 2021-06-29; accepted: 2021-07-02 is studying at a school, his or her mother usually cooperates with teachers to promote the child's education activities or possible issues [1,2] . In effect, globally speaking, mothers and teachers could be seen as the main guardians of students.…”
Section: Introductionmentioning
confidence: 99%